K4Cu3(C3N3O3)2X (X = Cl, Br): strong anisotropic layered semiconductors containing mixed p–p and d–p conjugated π-bonds. Issue 83 (18th September 2020) - Kang, Kaijin; Liang, Fei; Meng, Xianghe; Tang, Jian; Zeng, Tixian; Xia, Mingjun; Lin, Zheshuai; Yin, Wenlong; Bin, Kang
Abstract : Metal cyanurates K4 Cu3 (C3 N3 O3 )2 X (X = Cl, Br) containing π-conjugated anions are synthesized in flame-sealed silica tubes and they exhibit 2D graphene-like layered structures and intriguing semiconductor behaviors. Abstract : 2D materials are gaining more and more interest owing to their promising applications in future electronic industry. Here, two new quasi-2D metal cyanurates, K4 Cu3 (C3 N3 O3 )2 X (X = Cl, Br), were grown and characterized for the first time. They belong to the trigonal P 3̄ m 1 space group and feature an infinite layer, constructed by p–p conjugation in the (C3 N3 O3 ) planar six-membered-rings and d–p conjugation in the N–Cu–N linear chains. Moreover, they are indirect semiconductors with suitable bandgaps of 3.5 eV, locating between g-C3 N4 and h-BN. The electronic states and anisotropic optical responses were also studied through theoretical calculations.